Socioeconomic disparities in physical activity, sedentary behavior and sleep patterns among 6- to 9-year-old children from 24 countries in the WHO European region - Musić Milanović, Sanja; Buoncristiano, Marta; Križan, Helena; Rathmes, Giulia; Williams, Julianne; Hyska, Jolanda; Duleva, Vesselka; Zamrazilová, Hana; Hejgaard, Tatjana; Jørgensen, Maja Baeksgaard; Salanave, Benoît; Shengelia, Lela; et al. (Obesity reviews, 2021)
Physical activity, sedentary behavior, and sleep are important predictors of children's health. This paper aimed to investigate socioeconomic disparities in physical activity, sedentary behavior, and sleep across the WHO European region. This cross-sectional study used data on 124,700 children aged 6 to 9 years from 24 countries participating in the WHO European Childhood Obesity Surveillance Initiative between 2015 and 2017. Socioeconomic status (SES) was measured through parental education, parental employment status, and family perceived wealth. Overall, results showed different patterns in socioeconomic disparities in children's movement behaviors across countries. In general, high SES children were more likely to use motorized transportation. Low SES children were less likely to participate in sports clubs and more likely to have more than 2 h/day of screen time. Children with low parental education had a 2.24 [95% CI 1.94-2.58] times higher risk of practising sports for less than 2 h/week. In the pooled analysis, SES was not significantly related to active play. The relationship between SES and sleep varied by the SES indicator used. Importantly, results showed that low SES is not always associated with a higher prevalence of "less healthy" behaviors. There is a great diversity in SES patterns across countries which supports the need for country-specific, targeted public health interventions.
Keywords: obezita dětí a dospívajících; Sedentary Behavior; dítě; Social Class; sedavý životní styl; průřezové studie; lidé; cvičení; World Health Organization; Světová zdravotnická organizace; Cross-Sectional Studies; spánek; Socioeconomic Factors; Sleep; společenská třída; Child; socioekonomické faktory; Exercise; chování dětí; Child Behavior; Pediatric Obesity; Humans